Pengaruh Keterampilan Mengajar Guru, Disiplin Belajar, dan Minat Belajar Terhadap Prestasi Belajar IPS Siswa Kelas VII MTs Darun Najah Ngijo Karangploso Malang - Indah Iswidia (Jurnal Penelitian dan Pendidikan IPS, 2022)
Teaching and learning activities are the most basic activities in the whole educational process in school. This means that the success or failure of achieving educational goals depends a lot on how the learning process is experienced by students. The objectives of this research were: 1) to analyze the effect of teacher’s teaching skill, learning discipline, and learning interest on the learning achievement. 2) to analyze the teacher’s teaching skill on the learning achievement. 3) to analyze the learning discipline on the learning achievement. 4) to analyze the effect of learning interest on the learning achievement. This research belongs to quantitative research. The sample of this research were the students of VII grade at MTs Darun Najah Karangploso Malang. This research applied multiple linier regression method. The basis of decision making for the proposed hypothesis testing is as follows: Anova test results obtained an F-count score is 2,957 with a significant level of .040b because the significant level is smaller than 0.05, then the results of this study are: there is a significant effect simultaneously among Teacher Teaching Skills, Learning Disciplines, and Learning Interests on Student Learning Achievement. T-count value for variable X1 (Teacher Teaching Skills) is 1,668 with a significant level of .050 because the significant level is smaller than 0.05, then variable X1 (Teacher Teaching Skills) affects variable Y (learning achievement). So, there is a partially significant effect of Teacher Teaching Skills on learning achievements. T-count for variable X2 (Learning Discipline) of 2,283 with a significant rate of .026. Because the significant level is less than 0.05, the variable X2 (Learning Discipline) has an effect with variable Y (learning achievement). So, there is a partially significant effect on students' perception of learning disciplines on learning achievement. T-count value for variable X3 (Learning Interest) of 2,009 with a significant rate of .049. Because the significant level is less than 0.05, the variable X3 (Learning Interest) has an effect with variable Y (learning achievement). So, there is a partially significant effect on students' perception of learning interest in learning achievement. This study indicates that Teacher Teaching Skills as one of the external factors that affect students' learning achievement in Social Sciences subject (IPS). This researcher also proves that learning discipline as one of the external factors from within students has an effect on learning achievement, obedience to learning activities and adherence to school discipline. This research also proves that the interest in learning as one of the factors from within the student has an effect on the student's learning achievement.